Heterogeneous baroreflex control of sympathetic action potential subpopulations in humans. (6th April 2020) - Klassen, Stephen A.; Moir, M. Erin; Usselman, Charlotte W.; Shoemaker, J. Kevin
Abstract : Key points: Emission patterns in muscle sympathetic nerve activity stem from differently sized action potential (AP) subpopulations that express varying discharge probabilities. The mechanisms governing these firing behaviours are unclear. This study investigated the hypothesis that the arterial baroreflex exerts varying control over the different AP subpopulations. During baseline, medium APs expressed the greatest baroreflex slopes, while small and large APs exhibited weaker slopes. On going from baseline to lower body negative pressure (LBNP; simulated orthostatic stress), baroreflex slopes for some clusters of medium APs expressed the greatest increase, while slopes for large APs also increased but to a lesser degree. A subpopulation of previously silent larger APs was recruited with LBNP but these APs expressed weak baroreflex slopes. The arterial baroreflex heterogeneously regulates sympathetic AP subpopulations, exerting its strongest effect over medium APs. Weak baroreflex mechanisms govern the recruitment of latent larger AP subpopulations during orthostatic stress. Abstract: Muscle sympathetic nerve activity (MSNA) occurs primarily in bursts of action potentials (AP) with subpopulations that differ in size and discharge probabilities. The mechanisms determining these discharge patterns remain unclear. This study investigated the hypothesis that variations in AP discharge are due to subpopulation‐specific baroreflex control. We employed multi‐unit microneurography and a continuous wavelet analysis approach to extract sympathetic APs in 12 healthy individuals during baseline (BSL) and lower body negative pressure (LBNP; ‐40, ‐60, ‐80 mmHg). For each AP cluster, the baroreflex threshold slope was measured from the linear regression between AP probability (%) and diastolic blood pressure (mmHg). During BSL, the baroreflex exerted non‐uniform regulation over AP subpopulations: medium‐sized AP clusters expressed the greatest slopes while clusters of small and large APs expressed weaker slopes. On going from BSL to LBNP, the baroreflex slopes for each AP subpopulation were modified differently. Baroreflex slopes (%/mmHg) for some medium APs (cluster 5: −4.4 ± 4 to −9.1 ± 5) expressed the greatest increase with LBNP, while slopes for large APs (cluster 9: −1.3 ± 1 to −2.6 ± 2) also increased, but to a lesser degree. Slopes for small APs present at BSL exhibited reductions with LBNP (cluster 2: −3.9 ± 3 to −2.2 ± 3). Larger previously silent AP clusters recruited with LBNP expressed weak baroreflex regulation (cluster 14: −0.9 ± 1%/mmHg). The baroreflex exerts the strongest control over medium‐sized APs. Augmenting baroreflex gain and upward resetting of discrete AP subpopulations active at BSL, as well as recruiting larger previously silent APs with weak baroreflex control, facilitates elevated MSNA during orthostatic stress. Key points: Emission patterns in muscle sympathetic nerve activity stem from differently sized action potential (AP) subpopulations that express varying discharge probabilities. The mechanisms governing these firing behaviours are unclear. This study investigated the hypothesis that the arterial baroreflex exerts varying control over the different AP subpopulations. During baseline, medium APs expressed the greatest baroreflex slopes, while small and large APs exhibited weaker slopes. On going from baseline to lower body negative pressure (LBNP; simulated orthostatic stress), baroreflex slopes for some clusters of medium APs expressed the greatest increase, while slopes for large APs also increased but to a lesser degree. A subpopulation of previously silent larger APs was recruited with LBNP but these APs expressed weak baroreflex slopes. The arterial baroreflex heterogeneously regulates sympathetic AP subpopulations, exerting its strongest effect over medium APs. Weak baroreflex mechanisms govern the recruitment of latent larger AP subpopulations during orthostatic stress.